Validation of the Ohio Youth Assessment System Dispositional Tool (OYAS-DIS) an examination of race and gender differences - Campbell, Christina A. (Youth violence and juvenile justice, 2020)
The Ohio Youth Assessment System-Disposition Tool (OYAS-DIS) is a juvenile risk assessment that is used in numerous states and jurisdictions to assess criminogenic risk of juvenile offenders. Still, there is little published research on the predictive validity of the tool. The purpose of the current study was to examine the predictive validity of OYAS-DIS, with a specific focus on understanding prediction of recidivism across racial and gender subgroups. The sample consisted of 4,383 youth that received a court petition in a single large Midwestern county juvenile court. The findings indicated that the OYAS-DIS was a statistically significant predictor of recidivism across all racial and gender subgroups. However, there was statistically significant variation in predictive validity across subgroups. For instance, the tool was a statistically significantly better predictor of recidivism for White males as compared to Black male youth. There was also statistically significant variation in the predictive validity of certain domains (e.g., juvenile justice history) on the OYAS-DIS across racial and gender subgroups. Implications of research favor the use of the OYAS-DIS to predict recidivism for adjudicated juveniles.